2004
DOI: 10.1152/ajprenal.00342.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent expression of EDG family receptors and mesangial cell proliferation: role in lysophosphatidic acid-mediated cell growth

Abstract: Lysophosphatidic acid (LPA), a major member of the bioactive lysophospholipids in serum, possesses diverse physiological activities including cell proliferation. Recently, three endothelial differentiation gene (EDG) family receptors, including EDG-2 (LPA1), EDG-4 (LPA2), and EDG-7 (LPA3), have been identified as LPA receptors. The role of LPA and their receptors in mesangial cell physiology is not clearly understood. This study examined the expression profile of EDG receptors as a function of cell density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…However, additional studies on the hyperproliferative factors and the molecular mechanisms involved are needed to develop the most efficient and effective treatment strategy for DN. According to several studies 9,10,28 , including the present study, LPA exerts a pro-proliferative effect on renal mesangial cells. Moreover, in our previous study, the kidney cortex of diabetic mice showed proliferative activity with high levels of LPA 12 .…”
Section: Discussionsupporting
confidence: 62%
“…However, additional studies on the hyperproliferative factors and the molecular mechanisms involved are needed to develop the most efficient and effective treatment strategy for DN. According to several studies 9,10,28 , including the present study, LPA exerts a pro-proliferative effect on renal mesangial cells. Moreover, in our previous study, the kidney cortex of diabetic mice showed proliferative activity with high levels of LPA 12 .…”
Section: Discussionsupporting
confidence: 62%
“…Six G protein-coupled receptors specific for LPA are distributed widely in animal tissues and organs (Ishii et al, 2009;Noguchi et al, 2009). In the kidney, LPA 1 , LPA 2 , LPA 3 and LPA 4 have been characterized, and their physiological and pathophysiological roles were postulated in the excretion of wastes (Xing et al, 2004;Pradère et al, 2008). In fact, LPA stimulated the proliferation and contraction of rat glomerular mesangial cells through activation of an LPA receptor (Inoue et al, 1995a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological features of the glomeruli during the progression of DN include mesangial expansion, thickening of the basement membrane, loss of podocytes, and glomerulosclerosis [ 3 , 33 ]. Several studies, including our previous report, have demonstrated that LPA induces the hyperproliferation of mesangial cells [ 7 , 34 36 ], and that the pharmacological blockade of LPA/LPAR signaling inhibits renal fibrosis and improves DN in diabetic mice [ 10 , 11 , 37 ]. Consistent with these reports, it has been demonstrated that the levels of LPA are significantly increased in the glomeruli of diabetic mice [ 38 , 39 ] and high-fat diet-induced obese mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%